Human evolution : trails from the past - Cela Conde, Camilo José (Oxford biology., 2007)
This book is intended as a comprehensive overview of hominid evolution, synthesising data and approaches from physical anthropology, genetics, archaeology, psychology and philosophy. Human evolution courses are now widespread and this book has the potential to satisfy the requirements of most, particularly at the advanced undergraduate and graduate level. It is based on a translation, albeit with substantial modification, of a successful Spanish language book. - ;Human Evolution provides a comprehensive overview of hominid evolution, synthesising data and approaches from fields as diverse as p.